2017
DOI: 10.1158/1538-7445.sabcs16-p6-02-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-02-01: Metabolic stress induces GD2 expression and cancer stem cell phenotype in triple negative breast cancer

Abstract: Breast cancer stem cells (BCSCs) have been characterized as a fraction of cells in primary tumors that are drug resistant and have metastatic potential. Ganglioside GD2 has been shown by us and others as a marker for BCSCs. Furthermore, nutrient deprivation associated metabolic stress seen during tumor progression is reportedly associated with the cancer stem cell phenotype. We hypothesized that metabolic stress could induce spontaneous generation of GD2+ BCSCs during tumor progression. To test our hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 36 , 37 More specifically, cellular hypoxia can induce expression of GD3S 38 and also Sialin, 39 a sialic acid transporter, thereby enhancing expression of sialogangliosides in tumor cells. Finally, oxidative stress caused by nutrient deprivation was found to induce expression of G D2 in breast cancer cells, 40 , 41 concomitant with a cancer stem cell‐like phenotype. 42 Overall, it is a common observation that ganglioside expression patterns in tumor cells vary with environmental conditions, as mimicked in vitro by cellular confluency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 36 , 37 More specifically, cellular hypoxia can induce expression of GD3S 38 and also Sialin, 39 a sialic acid transporter, thereby enhancing expression of sialogangliosides in tumor cells. Finally, oxidative stress caused by nutrient deprivation was found to induce expression of G D2 in breast cancer cells, 40 , 41 concomitant with a cancer stem cell‐like phenotype. 42 Overall, it is a common observation that ganglioside expression patterns in tumor cells vary with environmental conditions, as mimicked in vitro by cellular confluency.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, oxidative stress caused by nutrient deprivation was found to induce expression of G D2 in breast cancer cells, 40,41 concomitant with a cancer stem cell-like phenotype. 42 Overall, it is a common observation that ganglioside expression patterns in tumor cells vary with environmental conditions, as mimicked in vitro by cellular confluency.…”
Section: Confluency Affects In Vitro Cytolysis Of Os Cells By G D2 -Specific Car T Cellsmentioning
confidence: 98%
“…Interestingly, the agent was found to be safe in mice [58]. BMS-345541 can also suppress breast tumorigenesis and metastases by targeting GD2+ cancer stem cells [59]. In another study, BMS-345541 was found to reduce proliferation and induce apoptosis in PC-3 cells [60].…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…• BMS-345541: Selectively targets an allosteric site of IKKα (IC 50 : 4 μM) and of IKKβ (IC 50 : 0.3μM) [57]; suppressed breast tumorigenesis and metastases by targeting GD2+ cancer stem cells [59]; inhibited EMT, induced apoptosis and suppressed proliferation of prostate cancer cells in a dose-dependent manner [60]; inhibited constitutive IKK activity and melanoma cell survival both in vitro and in vivo [61]; induced mitochondria-mediated apoptosis in melanoma cells [61].…”
Section: Abbreviationsmentioning
confidence: 99%